Distribution Characteristics of Partial Discharge Radio Frequency Signal in Transformer Tank and Bushing - Hui HUANG; Zhihao YANG; Jianguo WEI; Hui DENG; Yi LIU (Zhongguo dianli)
The external partial discharge (PD) radio frequency (RF) detection method is suitable for equipment in operation, and has become one of the important means to perceive the insulation defects of transformer and bushing. The detection sensitivity is affected by the matching of sensor installation position and polarization direction. In order to improve the sensitivity of the external RF detection method, this paper studies the amplitude distribution characteristics of the RF signal when the partial discharge electromagnetic wave in the transformer tank propagates through the bushing to the external space. Firstly, the propagation simulation model of partial discharge electromagnetic wave under bushing is established. Secondly, the dynamic process of electromagnetic wave propagation is shown by chromaticity diagram. Thirdly, the electric field intensity waveform of RF signal and the polarization direction of electric field intensity at typical locations outside the bushing are analyzed. Finally, partial discharge test and RF signal measurement are carried out, and the amplitude distribution characteristics and polarization characteristics of RF signal are verified by the measurement results of biconical antenna. The simulation results show that the electromagnetic wave propagates outward with the bushing grounding flange and the bushing top as the center; strong RF signals are measured near the two positions using the biconical antenna; the measured RF signal is the strongest when the polarization direction of the biconical antenna is parallel to the axial direction of the bushing. This conclusion is significant for improving the sensitivity of transformer and bushing partial discharge radio frequency detection.